Risk factors for hospitalisation and poor outcome with pandemic A/H1N1 influenza: United Kingdom first wave (May–September 2009). Issue 7 (13th July 2010) - Nguyen-Van-Tam, J S; Openshaw, P J M; Hashim, A; Gadd, E M; Lim, W S; Semple, M G; Read, R C; Taylor, B L; Brett, S J; McMenamin, J; Enstone, J E; Armstrong, C; et al.
Abstract : Background: During the first wave of pandemic H1N1 influenza in 2009, most cases outside North America occurred in the UK. The clinical characteristics of UK patients hospitalised with pandemic H1N1 infection and risk factors for severe outcome are described. Methods: A case note-based investigation was performed of patients admitted with confirmed pandemic H1N1 infection. Results: From 27 April to 30 September 2009, 631 cases from 55 hospitals were investigated. 13% were admitted to a high dependency or intensive care unit and 5% died; 36% were aged <16 years and 5% were aged ≥65 years. Non-white and pregnant patients were over-represented. 45% of patients had at least one underlying condition, mainly asthma, and 13% received antiviral drugs before admission. Of 349 with documented chest x-rays on admission, 29% had evidence of pneumonia, but bacterial co-infection was uncommon. Multivariate analyses showed that physician-recorded obesity on admission and pulmonary conditions other than asthma or chronic obstructive pulmonary disease (COPD) were associated with a severe outcome, as were radiologically-confirmed pneumonia and a raised C-reactive protein (CRP) level (≥100 mg/l). 59% of all in-hospital deaths occurred in previously healthy people. Conclusions: Pandemic H1N1 infection causes disease requiring hospitalisation of previously fit individuals as well as those with underlying conditions. An abnormal chest x-ray or a raised CRP level, especially in patients who are recorded as obese or who have pulmonary conditions other than asthma or COPD, indicate a potentially serious outcome. These findings support the use of pandemic vaccine in pregnant women, children <5 years of age and those with chronic lung disease.